Juventudes, afetos e linguagem: o saber discursivo e a formulação de sentidos sobre o amor a partir da fala de jovens acadêmicos - Moraes, Magna Maricelle Fernandes (2014)
This thesis has the objective of establishing a discussion about the discursive knowledge (mastery of the interdiscourse) and the formulation of meanings (mastery of the intradiscourse) concerning the love theme, considered to be the object of the discourse, starting from the speech of young undergraduation students. Our purpose, in other words, is to try to understand how the meanings about love are built starting from interviews made with two young students from the two undergraduation courses of the Federal University of Ceara-UFC - Home Economics graduation course and Letters Graduation Course – besides delineating an analysis about the constituent meanings of a discursive memory about love. As we are committed with the theoretical methodological assumptions of the French norms in Discourse Analysis, the love here is thought of as the result of historical processes of signification that are made permanent to and by the subject speaker, consequently is taken as a discursive object. Based on these presuppositions, we work with the categories youth, love and discourse (interdiscourse and intradiscourse). The first category is thought of in light of scholars like Bordieu (1983), Abramo (1994), Ariès (1981), Muchow (1968), Matza (1968), Pais (2003), Groppo (2000), more concerned with the areas of Sociology and Education, besides thinkers concerned with the field of History, like Leuchtenburg (1976) and Hobsbawm (1995). The love theme is marked out with basis on the work of authors like the Swiss historian Rougemont (2003); in the reflections of the writers and essayists Paz (1994) and Bruckner (2011); in considerations advocated by Luhmann (1991) and the ideas proposed by the Brazilian historian Del Priore (2012) and by Chauí (1991), besides the theoretical view of the sociologists Giddens (1993) and Bauman (2004). Still in what the theme is concerned, we immerse ourselves in texts of consecrated authors in the field of Literature being them of European, American or Brazilian origin like Shakespeare, Jack Kerouac, Nelson Rodrigues, Adélia Prado, among others, besides references to the Popular Brazilian Music and the cinematographic art. The last category – the discourse (interdiscourse and intradiscourse) – configures itself as a postulate of the AD, that is seen here from the theorethical-metodological bias proposed by Orlandi (2002). As results, we have concluded that the discourses of the young undergraduation students sometimes tend to bring into evidence negative aspects which would singularize the transformations occurred in the context of the love relationships; sometimes, on the contrary, highlight positive asoects of these changes. The first ones would be, in the discursive perspective of the female/male young students, the instability, the non-commitment with the other, the detachment, the ebsence of “true” love; whereas the positive are directly related with the advances concerning women’s freedom of speech and the marginalized sex minorities considered by them.